China’s Economic Growth - 21st Century Puzzle - Awan , Abdul Ghafoor (Global Disclosure of Economics and Business, 2013)
China’s fast economic growth since 1960s was the result of gradual shift in its economic system, open door policy and its accession to the world trade organization. The institutional reforms and access to foreign markets has been followed by investment strategies expanded 45% of Chinese GDP during last 40 years. The consistent vertical economic growth has no precedent in the economic history of the world. China has increased its share in world trade from 0.5% in 1960 to 10% in 2010 and accumulated foreign exchange reserves of US3.19 trillion by March 2013. It is not less than a miracle. The objective of this study is to investigate into the Chinese labour productivity and output in the short and long-run perspective to detect the real source of Chinese economic growth. Our study is spread over a period starting from 1962 to 2010 because of political and economic stability with minor crisis. The data was taken from China Bureau of National Statistics, IMF, World Bank and relevant research Journals and books. The variables included in this study are: labour productivity, investment, exports, R&D expenses, capital stock, open door policy, real exchange rate and US GDP. The VAR model proposed by Johansen (1988), Johansen and Juselius (1990,1994) and Hendry and Mizon (1993) was used to measure the nature of relations among the above variables. Different tests including unit root test were applied to test the stability of the model. The Econometric results show that international trade and investment in capital stock and R&D expenses by Chinese Government are the major determinants, which are responsible for enhancing labour productivity and output in the long-run, Similarly, real exchange rate appears as an important determinant to explain change in output in the long-run. US GDP has played no role in explaining Chinese output growth. JEL Classification Code: F43; O47